TERMS OF ADDRESS IN PESISIR BARUS NORTH SUMATERA - PUTRI MAYASARI TANJUNG; ZAINUDDIN ZAINUDDIN; AMRIN SARAGIH (State University of Medan, 2021)
The writer was found the result of this study about Terms of Address in Pesisir Barus Notrth Sumatera Kecamatan Barus, Kabupaten Tapanuli Tengah. this study aims to determine the kinds and factors of using Address Terms in Pesisir Barus community. And the data use by applying descriptive qualitative and quantitative method. The source of data was taken from the interviewing, video, recording and conversation in community. The technique for analyzing the data is descriptive qualitative research based on Wardaugh’s. The result of this reserach was kinds, factors and function in Pesisir Barus Community. The most dominant kinds the terns of address are used by pesisir barus community is RT (62 times), the most dominant rarely used by pesisir barus community is KT (56 times), PN (16 times), FN (11 times), and MT (2 times), IT (4 times) is seldom used by Pesisir Barus Community. There are four kinds factors and function of the terns of address in Pesisir Barus Community can be divided as G (Gender), A (Age), FR (Family Relationship). R (Respect). With the total factors of address terms used by Pesisir Barus Community was analysis G (27 times), A (28 times), FR (36 times), R (60 times).